Effect of Concentration of Pectinase on Clarification and Ascorbic Acid of Lemon Ginger Drink - Chrismita B. Lusihanne; Maria Herawati (Universitas Tadulako, 2020)
Lemon ginger drink is a herbal drink which contains many antioxidant and ascorbic acid that good for health. However, the murky appearance of the lemon ginger drink causes a lack of consumer interest especially young people in consuming this beverage. The murky in the lemon ginger drink is due to pectin content. Therefore, clarification is needed with the aid of a pectinase enzyme. The concentration of pectinase used in this study were 0; 0.04; 0.06; 0.08; 0.1; 0.1; and 0.12%; then incubated at 500 oC temperatures for 4 hours. The results showed that the proper concentration of pectinase in the clarification of lemon ginger drink was 0.08%. The concentration of the pectinase does not affect the ascorbic acid level of the lemon ginger drink.